Expression of NGF, BDNF and their receptors in subcutaneous adipose tissue of lactating cows. (October 2015) - Colitti, Monica; Loor, Juan J.; Stefanon, Bruno
Abstract: Currently, there are no reports of neurotrophins in adipose tissue of cows. The distribution of nerve growth factor (NGF), brain-derived neurotrophic factor (BDNF) and their high-affinity tyrosine kinase receptors TrkA and TrkB, was investigated by immunohistochemical method in the subcutaneous adipose tissue of cow at mid-lactation. Results revealed the localization of NGF and BDNF along the plasma membrane and cytoplasm of adipocytes. Neurotrophin receptors TrkA and TrkB showed moderate and strong positive staining in adipocytes, respectively. The expression of NGF, BDNF, TRKB — but not of TRKA — was also confirmed at transcriptional level by RT-PCR analyses. Considering the involvement of BDNF on fat metabolism and of NGF on activation of the sympathetic response in human and rodents, these neurotrophins could be related to lipogenesis and lipolysis occurring during lactation in cows. The local production of these neurotrophins supports their potential paracrine function for the regulation of adipocyte activity and deserve further investigations. Highlights: NGF and BDNF are involved in fat metabolism and in activation of the sympathetic response. Immunohistochemistry revealed the localization of NGF and BDNF in subcutaneous adipocytes of lactating cows. Gene expression of NGF, BDNF and TrkB confirms their local production. Neurotrophins could be a paracrine factor involved in regulation of adipocyte activity.